Analyzing the Effect of People Utilizing Mobile Technology to Make Banking Services More Accessible - Zhu, Jiale; Wang, Manyi (Frontiers in Public Health, 2022)
Digital payments have the potential to make financial services more accessible to all people. The worldwide COVID-19 health crisis, as well as government reactions such as economic lockdowns, raised the need for contactless financial goods and services, hastening the transition to digital banking in many nations. Although the COVID-19 pendamic situation has increased the usage of digital finance, not all communities or customers have been able to quickly shift to digital financial goods and services. The word mobile banking refers to a widespread method of providing financial services and localization to customers. Because mobile banking is so important to both banks and users, it has been included in numerous literary works. As a result, embracing financial services via the m-banking platform is critical. This paper's technique is mostly descriptive research that investigates common views, current situations, modern tactics, tangible emerging consequences, etc. The main objective here is to analyze the benefits of the present by investigating the past. Since this paper analyzes what actually exists and is descriptive. The data is retrieved by conducting a cross-sectional survey method about different features that are relevant by sampling the population. The main aim of this study is to explore the adoption of mobile banking technology by consumers. Based on the values of different variables such as Affective commitment (AC), Transaction Convenience (TC), Perceived ease of use (PEU), Perceived Reliability (PR), Pre and Post Benefits (PPB) Service, system, and Information Quality (SSIQ), Bank Trust (BT), and Profitability(P), the interrelationship between them and the adoption of m-banking technique by the users in banking technology. The model is investigated by examining the hypothesis and identifying the relationship that exists between these different parameters. A simple linear regression method is implemented using the Statistical Package for the Social Sciences (SPSS) software.